SUSCEPTIBILITY STATUS OF XENOPSYLLA CHEOPS AND X ASTIATO DDT - KUMAR, ARVIND; KUMAR, KAUSHAL; SINGH, P. P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2007)
In the present study, the susceptibility status of two flea species namely Xenopsylla cheopis and X. astia, collected from Distt. Baghpat of western U.P. India has been discussed. The fleas were tested for 4% DDT by WHO standard methods for 1 hr. The Xenopsylla cheopis showed 82.69% mortality while X, astia showed 92.66%. Males were found more susceptible than females in both the species. The results showed that the fleas of Xenopsylla cheopis possessed a considerable degree of resistance to DDT. It is inferred that the fleas have been exposed to DDT in local environment due to various sanitary conditions.